Pengaruh Pengangguran Terhadap Kemiskinan Ditinjau Dari Perspektif Ekonomi Islam - Dini Anggraini; Muhammad Iqbal Fasa; Suharto Suharto (FEB Universitas Sultan Ageng Tirtayasa, 2023)
Poverty is a complex problem because it involves various aspects such as the right to food, health, education, employment, and so on. The formulation of the problem in this study is How the Effect of Unemployment on Poverty is reviewed from an Islamic Perspective and how is the Effect of the Open Unemployment Rate in Lampung Province in 2017. This study aims to determine the Effect of Unemployment on Poverty in an Islamic Perspective and to determine the effect of the Open Unemployment Rate in Lampung Province. year 2017.The research method used in this study is a quantitative method. The source of data used is secondary data published by the Central Statistics Agency. The results of this study indicate that the open unemployment rate by province in Sumatra is relatively varied. Aceh has the highest TPT, which is around 7.39 percent. Meanwhile, the lowest TPT was around 2.81 percent in Bengkulu. TPT Lampung is the fourth lowest TPT on the island of Sumatra at around 4.4 percent. And the unemployment rate is higher in urban areas as much as 6.49 percent than in rural areas the unemployment rate is only 3.61 percent.Efforts to reduce unemployment and poverty are equally important. If the population does not increase and people are not unemployed, it means they have jobs and income that can meet their needs. If the needs of life are met, the community will not be poor. So it can be said that with a low population and low unemployment, poverty is also low. Unemployment affects poverty, because if people do not have jobs and income, the necessities of life will not be fulfilled so they can be classified as poor people. Islam really hates poverty because according to Islam wealth is a blessing and gift from Allah SWT that must be grateful for by mankind, poverty must be eliminated because it can endanger faith, morals and morals and can even cause division in society.